A Comparative Study of the Concept of Khula’ in the Perspective of Sharia’ and the Legal System of Pakistan - Dr. Imran Hayat,; Dr. Mohsin Abbasi,; Mr. Rahim Ullah,; Dr. Adeeba Siddiqui,; Mr. Mufti Muhammad Usman Aslam, (Al-Qanṭara, 2022)
The study comparatively examines the concept of Khula’ (خلع) from the perspectives of Sharia (شریعہ) and the legal structure of Pakistan. The four prominent major Fiqhi schools of thought unanimously prohibit a Muslim woman to obtain Khula’ (خلع) without seeking the consent of her husband. However, the Maliki school of thought approve the role of intermediaries, the authority in form of the state, the court of the state or the spouses themselves in resolution to the dispute between the spouses, who can decide separation or union with the prior consent of the spouses. Moreover, the legal system of Pakistan also privileges women to get Khula’ (خلع) without their husband’s consent from the court. The paper analyses that the foundation of this law on Khula’ (خلع) is partially based on the fiqh rulings. Thus, the Pakistani courts seek the validity of its legal position in the rulings of the Maliki school of thought on the concept of Khula’ (خلع).